SOSIALISASI DAN PENGUATAN KELOMPOK TANI HUTAN TERKAIT KONSERVASI KAWASAN HUTAN ADAT DI DESA HUTUMURI KECAMATAN LEITIMUR SELATAN PULAU AMBON - Moda Talaohu; Rohny S. Maail; Sofia Mustamu; Miranda H. Hadijah; Lydia Parera (Universitas Pattimura, 2026)
Forest degradation in the Maluku region, particularly on Ambon Island—driven by land-use conversion, unregulated deforestation, and a deficiency in ecological awareness—has posed a significant threat to environmental equilibrium. Hutumuri Village is a designated Customary Forest area, formally recognized under the Decree of the Minister of Environment and Forestry Number SK.7876/MENLHK-PSKL/PKTH/PSL.1/12/2020, enacted on December 28, 2020. Geographically, Hutumuri is situated across coastal and hilly terrains, rendering it highly vulnerable to flooding, landslides, coastal erosion, and the depletion of water resource quality. Consequently, community outreach initiatives—utilizing educational lectures, participatory discussions, and pre-test and post-test evaluations—were implemented to enhance knowledge and cultivate collective responsibility toward forest conservation. The results of this community service program indicate a marked improvement in public understanding and a positive shift in attitudes, serving as a foundational element for strengthening the long-term environmental sustainability of the village.